A qualitative study exploring physicians’ perceptions on the role of community pharmacists in Dubai - Rayes IK (Pharmacy Practice, 2016)
Objective: The aim of this study is to explore the perceptions of physicians operating within the boundaries of Dubai on the role of community pharmacists. Methods: Semi-structured interviews were done with 12 physicians working within the boundaries of Dubai Health Authority. Interviews mainly focused on understanding the perceptions of physicians on the role of community pharmacists in addition to willingness to integrating pharmacists in patient care process. Results: Key findings show that all interviewees agree that community pharmacists are important healthcare professionals. However, 7 physicians restrict the role of pharmacists to dispensing medicines. Physicians in Dubai are willing to collaborate with pharmacists, but more than half of them (7) think that pharmacists might interfere with their jobs. Conclusion: The study concludes that all informants agree that collaboration between community pharmacists and physicians definitely enhances patients’ drug therapy outcomes.